Low power consumption mini rotary actuator with SMA wires. (29th September 2017) - Manfredi, Luigi; Huan, Yu; Cuschieri, Alfred
Abstract: Shape memory alloys (SMAs) are smart materials widely used as actuators for their high power to weight ratio despite their well-known low energy efficiency and limited mechanical bandwidth. For robotic applications, SMAs exhibit limitations due to high power consumption and limited stroke, varying from 4% to 7% of the total length. Hysteresis, during the contraction and extension cycle, requires a complex control algorithm. On the positive side, the small size and low weight are eminently suited for the design of mini actuators for robotic platforms. This paper describes the design and construction of a light weight and low power consuming mini rotary actuator with on-board contact-less position and force sensors. The design is specifically intended to reduce (i) energy consumption, (ii) dimensions of the sensory system, and (iii) provide a simple control without any need for SMA characterisation. The torque produced is controlled by on-board force sensors. Experiments were performed to investigate the energy consumption and performance (step and sinusoidal angle profiles with a frequency varying from 0.5 to 10 Hz and maximal amplitude of 15 ◦ ). We describe a transient capacitor effect related to the SMA wires during the sinusoidal profile when the active SMA wire is powered and the antagonist one switched-off, resulting in a transient current time varying from 300 to 400 ms.